Age-Dependent Fecal Bacterial Correlation to Inflammatory Bowel Disease for Newly Diagnosed Untreated Children - Felix Chinweije Nwosu; Lill-Therse Thorkildsen; Ekaterina Avershina; Petr Ricanek; Gøri Perminow; Stephan Brackmann; Morten H. Vatn; Knut Rudi (Gastroenterology Research and Practice)
The knowledge about correlation patterns between the fecal microbiota and inflammatory bowel diseases (IBD)—comprising the two subforms Crohn's disease (CD) and ulcerative colitis (UC)—for newly diagnosed untreated children is limited. To address this knowledge gap, a selection of faecal specimens (CD, n=27 and UC, n=16) and non-IBD controls (n=30) children (age < 18 years) was analysed utilising bacterial small subunit (SSU) rRNA. We found, surprising age dependence for the fecal microbiota correlating to IBD. The most pronounced patterns were that E. coli was positively (R2=0.16, P=0.05) and Bacteroidetes, negatively (R2=0.15, P=0.05) correlated to age for CD patients. For UC, we found an apparent opposite age-related disease correlation for both Bacteroides and Escherichia. In addition, there was an overrepresentation of Haemophilus for the UC children. From our, results we propose a model where the aetiology of IBD is related to an on-going immunological development in children requiring different age-dependent bacterial stimuli. The impact of our findings could be a better age stratification for understanding and treating IBD in children.